Targeting gut-microbiota for gastric cancer treatment: a systematic review - Marashi, Amir; Hasany, Saina; Moghimi, Sadra; Kiani, Reza; Mehran Asl, Sina; Dareghlou, Yasamin Alavi; Lorestani, Parsa; Varmazyar, Shirin; Jafari, Fatemeh; Ataeian, Shakiba; Naghavi, Kiana; Sajjadi, Seyed Mohammad; et al. (Frontiers in Medicine, 2024)
Background Preclinical research has identified the mechanisms via which bacteria influence cancer treatment outcomes. Clinical studies have demonstrated the potential to modify the microbiome in cancer treatment. Herein, we systematically analyze how gut microorganisms interact with chemotherapy and immune checkpoint inhibitors, specifically focusing on how gut bacteria affect the pharmacokinetics and pharmacodynamics of cancer treatment. Method This study searched Web of Science, Scopus, and PubMed until August 2023. Studies were screened by their title and abstract using the Rayyan intelligent tool for systematic reviews. Quality assessment of studies was done using the JBI critical appraisal tool. Result Alterations in the gut microbiome are associated with gastric cancer and precancerous lesions. These alterations include reduced microbial alpha diversity, increased bacterial overgrowth, and decreased richness and evenness of gastric bacteria. Helicobacter pylori infection is associated with reduced richness and evenness of gastric bacteria, while eradication only partially restores microbial diversity. The gut microbiome also affects the response to cancer treatments, with higher abundances of Lactobacillus associated with better response to anti-PD-1/PD-L1 immunotherapy and more prolonged progression-free survival. Antibiotic-induced gut microbiota dysbiosis can reduce the anti-tumor efficacy of 5-Fluorouracil treatment, while probiotics did not significantly enhance it. A probiotic combination containing Bifidobacterium infantis, Lactobacillus acidophilus, Enterococcus faecalis, and Bacillus cereus can reduce inflammation, enhance immunity, and restore a healthier gut microbial balance in gastric cancer patients after partial gastrectomy. Conclusion Probiotics and targeted interventions to modulate the gut microbiome have shown promising results in cancer prevention and treatment efficacy. Systematic review registration:https://osf.io/6vcjp.